Variability of extracellular vesicle release during storage of red blood cell concentrates is associated with differential membrane alterations, including loss of cholesterol-enriched domains - Ghodsi, Marine; Cloos, Anne-Sophie; Mozaheb, Negar; Van Der Smissen, Patrick; Henriet, Patrick; Pierreux, Christophe E.; Cellier, Nicolas; Mingeot-Leclercq, Marie-Paule; Najdovski, Tomé; Tyteca, Donatienne (Frontiers in Physiology, 2023)
Transfusion of red blood cell concentrates is the most common medical procedure to treat anaemia. However, their storage is associated with development of storage lesions, including the release of extracellular vesicles. These vesicles affect in vivo viability and functionality of transfused red blood cells and appear responsible for adverse post-transfusional complications. However, the biogenesis and release mechanisms are not fully understood. We here addressed this issue by comparing the kinetics and extents of extracellular vesicle release as well as red blood cell metabolic, oxidative and membrane alterations upon storage in 38 concentrates. We showed that extracellular vesicle abundance increased exponentially during storage. The 38 concentrates contained on average 7 × 1012 extracellular vesicles at 6 weeks (w) but displayed a ∼40-fold variability. These concentrates were subsequently classified into 3 cohorts based on their vesiculation rate. The variability in extracellular vesicle release was not associated with a differential red blood cell ATP content or with increased oxidative stress (in the form of reactive oxygen species, methaemoglobin and band3 integrity) but rather with red blood cell membrane modifications, i.e., cytoskeleton membrane occupancy, lateral heterogeneity in lipid domains and transversal asymmetry. Indeed, no changes were noticed in the low vesiculation group until 6w while the medium and the high vesiculation groups exhibited a decrease in spectrin membrane occupancy between 3 and 6w and an increase of sphingomyelin-enriched domain abundance from 5w and of phosphatidylserine surface exposure from 8w. Moreover, each vesiculation group showed a decrease of cholesterol-enriched domains associated with a cholesterol content increase in extracellular vesicles but at different storage time points. This observation suggested that cholesterol-enriched domains could represent a starting point for vesiculation. Altogether, our data reveal for the first time that the differential extent of extracellular vesicle release in red blood cell concentrates did not simply result from preparation method, storage conditions or technical issues but was linked to membrane alterations.